Vision Impairment and Productivity Among Female Garment Workers in Bangladesh: A Cohort Study. Issue 1 (January 2022) - Ahmed, Munir; Shefali, Mashuda Khatun; Husain, Lutful; Khondaker, Mahbuba; Alauddin, Mohammed; Hossain, Mohammad Awlad; Kabir, A.K.M. Nurul; Whitestone, Noelle; Cherwek, David Hunter; Congdon, Nathan; Patnaik, Jennifer L.
Abstract : Purpose: To assess the prevalence of near and correctable distance visual impairment among screened participants in the garment industry and to explore associations with income, age, and urban versus rural residence. Methods: Vision screenings were conducted at 4 garment factories, 2 urban and 2 rural locations during September and October 2019. Distance vision impairment was the presence of uncorrected vision of <6/12 in either eye, correctable to ≥6/7.5 with distance refraction. Near vision impairment was defined as 1 or more of the following: 1) either eye with presenting near vision 6/12 in the same eye; 2) having been prescribed near add spectacle power in examination records; and/or 3) clinical diagnosis of presbyopia at the time of screening. Demographic information and monthly income were self-reported by questionnaire completion. Results: Among 915 participating workers (100% female, 18 to 70 years), 29.2% (n = 267) and 26.8% (n = 245) had correctable distance and near vision impairment respectively. Prevalence of near vision impairment was significantly higher among rural residents (34.2%, n = 160), compared to urban (19.0%, n = 85, P  < 0.0001) with the largest differences in the 35 to 39 (68.2% vs 44.2%, P  = 0.0019) and 40+ (85.9 vs 48.9%, P  < 0.0001) year age ranges. Prevalence of near vision impairment was already high among urban (20.4%, n = 20) and rural (23.0%, n = 17) workers aged 30 to 34 years. In simple linear regression models, participants with near vision impairment earned $13.3 [standard error (SE) 2.44, P  < 0.0001] less per month than those without, while urban residents earned $40.6 (SE 1.74, P  < 0.0001) more than rural dwellers. In the final multivariate linear model, both near vision impairment ($6.51 lower monthly earnings, SE 1.84, P  = 0.0004) and urban residence ($43.2 higher monthly earnings, SE 2.39, P  < 0.0001) remained significantly associated with income. Conclusions: This study found high rates of near vision impairment among female garment workers, particularly rural dwellers, and at a younger age than expected. The high prevalence and association between near vision impairment and lower income suggest that focusing on industries with a high proportion of female workers, such as readymade garments, may be effective in addressing gender disparities in vision impairment and its economic impact.